The Effect Of Performance Allowance And Supervision On Employees Performance Of Bps North Sumatra With Motivation As Intervening Variable - Uswatun Hasanah; Teddy Chandra; Fatia Fatimah (SEAN Institute, 2023)
The purpose of this study was to analyze the effect of performance allowances, supervision and motivation on employee performance. This research was conducted on employees of the BPS of North Sumatra with a population of 799 people. The sample selection of 300 respondents was carried out using the proportionate stratified random sampling technique. The research instrument used was a questionnaire and the measurement of the variables was carried out using a Likert scale. Data analysis was carried out using the Structural Equation Model (SEM) method. The results of the analysis show that performance allowances and supervision have a significant positive effect on the motivation of BPS North Sumatra employees, as well as supervision and motivation which have a significant positive effect on the performance of BPS North Sumatra employees, however performance allowances have no significant effect on the performance of BPS North Sumatra employees.